Cytokine signaling regulating adipose stromal cell trafficking. (1st October 2016) - Zhang, Yan; Kolonin, Mikhail G.
ABSTRACT: Adipocyte progenitors, known as adipose stromal cells (ASC), can become mobilized, recruited by tumors, and contribute to cancer progression. Mechanisms underlying ASC trafficking have remained obscure. We recently reported that CXCL1 expressed by cancer cells chemoattracts ASC expressing CXCR1 in obesity. As a candidate mechanism of CXCL1 activation, we identified interleukin (IL)-22, systemic circulation of which is increased in obesity. It has been reported that IL-22 signaling through IL-22R is upstream of CXCL1. Here, we provide evidence that IL-22 expression by leukocytes infiltrating WAT and IL-22R expression by tumors is obesity-dependent. We propose that obesity-associated adipocyte death and the resulting recruitment of leukocytes triggers the IL-22 signaling cascade that induces CXCL1 secretion by cancer cells responsible for ASC trafficking to tumors.